Diabetes alters the association between high-density lipoprotein subfractions and carotid intima-media thickness: The Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). (November 2018) - Generoso, Giuliano; Bensenor, Isabela M; Santos, Itamar S; Santos, Raul D; Goulart, Alessandra C; Jones, Steven R; Kulkarni, Krishnaji R; Blaha, Michael J; Toth, Peter P; Lotufo, Paulo A; Bittencourt, Marcio Sommer
Introduction: High-density lipoprotein cholesterol comprises a group of heterogeneous subfractions that might have differential effects on atherosclerosis. Moreover, prior investigations suggest that the presence of diabetes (T2D) modifies the impact of some subfractions on atherosclerosis. In this study, we aimed to evaluate the association between high-density lipoprotein cholesterol subfractions and carotid intima-media thickness in the baseline assessment of the Brazilian Longitudinal Study of Adult Health participants from the São Paulo investigation centre. Methods: We evaluated 3930 individuals between 35 and 74 years without previous cardiovascular disease not using lipid-lowering drugs. High-density lipoprotein cholesterol subfractions (HDL2 -C and HDL3 -C) were measured by vertical ultracentrifugation (vertical auto profile). The relationship between each high-density lipoprotein cholesterol subfraction and carotid intima-media thickness was analysed by multiple linear regression models. Results: Total high-density lipoprotein cholesterol, as well as HDL2 -C and HDL3 -C, was negatively associated with carotid intima-media thickness after adjustment for demographic data (all p < 0.001) and traditional risk factors (all p < 0.05). When stratified by T2D status, the HDL2 -C/HDL3 -C ratio showed a negative association with carotid intima-media thickness in participants with T2D ( p = 0.032), even after fully controlling for confounding variables, including total high-density lipoprotein cholesterol. Conclusion: HDL2 -C, HDL3 -C and HDL2 /HDL3 -C ratio are inversely associated with carotid intima-media thickness after adjustment for traditional risk factors. Association of the HDL2 -C/HDL3 -C ratio is modified by the presence of diabetes, being more pronounced in diabetic individuals.